Volume 2: Nuclear Fuels, Research, and Fuel Cycle; Nuclear Codes and Standards; Thermal-Hydraulics 2021
DOI: 10.1115/icone28-65776
|View full text |Cite
|
Sign up to set email alerts
|

Research on Application of Additive Manufacturing Technology In Nuclear Fuel Assembly Field

Abstract: As one of the key technologies of the fourth industrial revolution, Additive Manufacturing (AM, also called 3D printing), which is the basis of innovation design with its high degree of manufacturing freedom, has been widely used in the construction field, aerospace field, automobile manufacturing field, biomedical field, etc. With the increasing maturity of additive manufacturing technology, it has been gradually used in the field of nuclear energy in order to realize design reform. Public reports have shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…AM is offering manufacturing sectors innovative approach to manufacture optimized, lightweight and high performing structures (e.g., bionic) [15,23,24] without direct increasing to time and costs [25]. Exemplary to studies [18,[26][27][28] AM is shown to improve performance and/or offer economic benefits for pressure vessels. Studies [19,29,30] on the other hand have demonstrated how different AM specially PBF and DED enhance performance (microstructure, mechanical properties) of additively manufactured IN718 parts.…”
Section: Prospects Of Additively Manufactured Inconel 718 Pressure Ve...mentioning
confidence: 99%
“…AM is offering manufacturing sectors innovative approach to manufacture optimized, lightweight and high performing structures (e.g., bionic) [15,23,24] without direct increasing to time and costs [25]. Exemplary to studies [18,[26][27][28] AM is shown to improve performance and/or offer economic benefits for pressure vessels. Studies [19,29,30] on the other hand have demonstrated how different AM specially PBF and DED enhance performance (microstructure, mechanical properties) of additively manufactured IN718 parts.…”
Section: Prospects Of Additively Manufactured Inconel 718 Pressure Ve...mentioning
confidence: 99%